PENGARUH GOOD CORPORATE GOVERNANCE DAN KEPEMILIKAN SAHAM PUBLIK TERHADAP TINGKAT PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Bobi, Yopinus; Relita, Dessy Triana; Suriyanti, Yulia; Astikawati, Yunita (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
Companies prioritize CSR out of awareness of social and environmental impacts, as well as to meet societal expectations, reduce reputational risks, and strengthen relationships with stakeholders. However, decisions related to CSR can be influenced by public share ownership, because public shareholders have different preferences from institutional or majority shareholders. This research aims to determine the influence of GCG practices and public share ownership on CSR disclosure. The research method used is quantitative using a survey approach. Data collection was carried out through purposive sampling, from 82 mining companies listed on the Indonesia Stock Exchange in 2021 and 2022, 76 companies were sampled. Multiple linear regression tests and simple linear regression tests are used as data analysis methods. Linear regression analysis shows that there is a positive and significant influence of audit committee size and ownership on all types of CSR, while the composition of public ownership has a significant negative influence. The composition of the independent board of commissioners and institutional ownership do not have a significant effect. These results indicate the need to consider GCG structure and share ownership in an effort to increase Corporate Social Responsibility disclosure.